Availability of credit and secured transactions in a time of crisis / edited by N. Orkun Akseli. - Akseli, N. Orkun (Nazim Orkun) (Cambridge University Press, 2013)
In the light of the financial crisis, it has become clear that the globalisation of financial markets has not been matched by the globalisation of legal certainty relating to financial transactions. The ability to give security influences not only the cost of credit but also, in some cases, whether credit will be available at all. Increasing the availability and lowering the cost of credit can make an important contribution to international and domestic economic development. Assessing the international challenges posed by inefficient secured credit laws, this book explores how these can be overcome to facilitate credit through legal reforms. Leading authorities in the field address the key issues surrounding the availability of credit, the role of banks in economic development and financial crises, UNCITRAL's legislative efforts, and international organisations and financial institutions and their involvement in the reform of secured transactions law.